Indigenous climate change mitigation strategies in tropical cities – a review - Akinkuolie, Timothy A.; Ogunbode, Timothy O.; Adekiya, Aruna O.; Fapohunda, Michael T. (Frontiers in Sustainable Cities, 2024)
Climate change poses numerous issues for indigenous populations in tropical cities worldwide, including reduced access to food, dwindling resources, and the proliferation of vector-borne illnesses. Indigenous communities are developing various mitigation and adaptation measures suitable for their distinct cultural and ecological demands. This study investigates the numerous indigenous climate change mitigation strategies (ICCMSs) being deployed in tropical cities, using secondary sources of data. The methodology involved a systematic review based on PRISMA guidelines, encompassing the identification, screening, eligibility, and inclusion of relevant literature. From an initial 1,202 sources, 452 were screened, and 104 met the inclusion criteria for full-text assessment. Findings indicate that common ICCMSs in tropical cities include the use of traditional knowledge systems and materials in urban green infrastructure projects, agroforestry, sustainable urban agriculture, urban afforestation and reforestation, and indigenous technologies and innovations in waste management practices. Indigenous peoples have benefited from greater education and understanding about climate change, empowering them to take action and lower their greenhouse gas (GHG) emissions. The study recommends that governments and international organizations support these mitigation efforts, incorporate them into public policy and urban planning for indigenous communities in tropical cities, and reduce global anthropogenic GHG emissions. Further studies are suggested to assess the effectiveness of these measures and their potential to enhance climate resilience in tropical cities.